Final business and regulatory impact assessment : the Electricity (Applications for Consent) Regulations 1990 and Electricity Works (Environmental Impact Assessment) (Scotland) Regulations 2017.: the Electricity (Applications for Consent) Regulations 1990 and Electricity Works (Environmental Impact Assessment) (Scotland) Regulations 2017. (2018) - Unknown
No abstract available